Kajian penambahan serbuk pegagan (Centella asiatica) terhadap mutu cookies tepung mocaf (modified cassava flour) - Mukminin, Amirul; Asmawati, Asmawati; Marianah, Marianah (Journal of Agritechnology and Food Processing, 2022)
Cookies are a type of biscuit made from wheat flour with a soft dough, high fat content, relatively crunchy, and dense texture. To increase the nutritional value and functional properties of cookies, it is necessary to add other ingredients such as pegagan plant. The pegagan plant contains chemical components that are good for human health such as calcium, ascorbic acid, and bioactive compounds such as triterpenoids and asiaticoside which have antioxidant activity. The purpose of this study was to determine the effect of the addition of pegagan powder on the quality of mocaf flour cookies and determine the percentage of addition of pegagan powder that was appropriate and preferred by the panelists. The method used in this study was an experimental method arranged in a completely randomized design with the addition of pegagan powder in the manufacture of cookies consisting of five treatments: P0 (100% mocaf flour/control), P1 (2.5% pegagan powder), P2 (5% pegagan powder), P3 (7.5% pegagan powder) and P4 (10% pegagan powder). The results of the measurement of chemical properties and organoleptic tests were analyzed using a further test of Honest Significant Difference at 5% level. Based on the results of the study, it was found that the addition of pegagan powder had a significant effect on all tested chemical properties (moisture content, ash content, vitamin C, and antioxidant activity) and also on taste, aroma, and color scores, but had no significant effect on cookies texture scores. In which, the higher the concentration of pegagan powder added, the water content, ash content, vitamin C content, and antioxidant activity increased, while the scores for aroma, taste and color tended to decrease. The best treatment favored by panelists was P3, with preferred taste, slightly favorable aroma, green appearance color, and slightly soft texture. The values of water content, ash content, vitamin C content, and P3 antioxidant activity were 8.36%; 3.08%; 0.38%; and 94.45%, respectively.